Genome-wide profiling of Sus scrofa circular RNAs across nine organs and three developmental stages - Liang, Guoming; Yang, Yalan; Niu, Guanglin; Tang, Zhonglin; Li, Kui (DNA research, 2017)
The spatio-temporal expression patterns of Circular RNA (circRNA) across organs and developmental stages are critical for its function and evolution analysis. However, they remain largely unclear in mammals. Here, we comprehensively analysed circRNAs in nine organs and three skeletal muscles of Guizhou miniature pig (S. scrofa), a widely used biomedical model animal. We identified 5,934 circRNAs and analysed their molecular properties, sequence conservation, spatio-temporal expression pattern, potential function, and interaction with miRNAs. S. scrofa circRNAs show modest sequence conservation with human and mouse circRNAs, are flanked by long introns, exhibit low abundance, and are expressed dynamically in a spatio-temporally specific manner. S. scrofa circRNAs show the greatest abundance and complexity in the testis. Notably, 31% of circRNAs harbour well-conserved canonical miRNA seed matches, suggesting that some circRNAs act as miRNAs sponges. We identified 149 circRNAs potentially associated with muscle growth and found that their host genes were significantly involved in muscle development, contraction, chromatin modification, cation homeostasis, and ATP hydrolysis-coupled proton transport; moreover, this set of genes was markedly enriched in genes involved in tight junctions and the calcium signalling pathway. Finally, we constructed the first public S. scrofa circRNA database, allowing researchers to query comprehensive annotation, expression, and regulatory networks of circRNAs.